Upaya Peningkatan Cakupan Kunjungan Calon Pengantin (CATIN) Untuk Melaksanakan Pemeriksaan Kesehatan dan Perencanaan Kehamilan Melalui Program SUSCATIN di PUSKESMAS Slempit Kabupaten Gresik Jawa Timur - Linda Andri Mustofa Mustofa (STIKES dan AKZI Karya Husada Kediri, 2023)
Abstract Indonesia is one of the countries with a high MMR, even the highest in Southeast Asia. Maternal death is caused by preventable factors. Planning a healthy pregnancy is an inexpensive way with minimal losses. SUSCATIN is a couple coaching program that can increase the readiness of the bride and groom in planning their reproductive functions, but the coverage is still low. Socialization or counseling is needed regarding the implementation of SUSCATIN so that the coverage of SUSCATIN can be increased. This community service activity aims to determine the effectiveness of counseling in increasing participants' knowledge about the implementation of SUSCATIN. The activity was carried out in Slempit Village, Gresik Regency, East Java Province from March 6 to April 8 2022 with the target of 20 pairs of prospective brides in the Slempit PUSKESMAS Slempit area, Gresik Regency. Evaluation of the impact of activities is measured using a questionnaire instrument that is tested for 2 times, namely the pre and post test. Data analysis was carried out by calculating the percentage showing the results of an increase in participants' knowledge after being given counseling. Counseling is a knowledge transfer activity from the speaker to the participants with material that has been prepared properly and is presented using an interactive question and answer lecture method using good media so that it is easy for participants to understand. With good knowledge, it is hoped that the behavior of following SUSCATIN will emerge actively and fully so that the bride and groom will be better prepared to face marriage both physically, mentally and reproductive health Keywords: SUSCATIN, Extension, Knowledge